2019
DOI: 10.1080/10406638.2019.1584576
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Recent Multicomponent Synthesis of Pyranopyrazoles

Abstract: Due to biological and medicinal properties of pyranopyrazoles, synthesis of these bioactive heterocycles has attracted the interest of medicinal and organic chemists. This review focuses on the recent developments in multicomponent synthesis of pyranopyrazole and spiroconjugated pyranopyrazole systems. The present review describes the literature reports for the period 2005 to 2018. These reported approaches were performed in the classical and nonclassical conditions, particularly recent reports includes protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 157 publications
(113 reference statements)
0
40
0
Order By: Relevance
“…All of the materials were of commercial reagent grade and were used without further purification. The synthesis and characterization of the studied compounds were previously reported [49]. Melting points of products were determined by Electro thermal 9200.…”
Section: Methodsmentioning
confidence: 99%
“…All of the materials were of commercial reagent grade and were used without further purification. The synthesis and characterization of the studied compounds were previously reported [49]. Melting points of products were determined by Electro thermal 9200.…”
Section: Methodsmentioning
confidence: 99%
“…1 ). Because of the great importance and numerous utilizations of pyranopyrazole and its derivatives, modifying the procedure for its synthesis are at the top of scientific research 3 , 4 . Using heterogeneous nanocatalyst to synthesize pyranopyrazole has attracted great importance among previous methods on account of high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Chief among these are multiple pharmacological and biological properties, such as antioxidant, antibacterial, anti-molluscicidal, analgesic, antiviral potential, and inhibitors of human checkpoint kinase-1 [9]. Upon an extensive literature review, it was confirmed that the wide-range of pyrano-[2,3-c]-pyrazoles activities are linked to the structural base core of the condensed pyrane and pyrazole [10]. In this regard, researchers expended efforts on the development of a single structural framework by associating both motifs (pyrane and pyrazole) in the hope of enhancing the biological activity and pharmacological properties of this compound [11].…”
Section: Introductionmentioning
confidence: 99%